Pengembangan Media Pembelajaran Interaktif Pada Mata Pelajaran Ilmu Pengetahuan Sosial Kelas VIII SMP Negeri 2 Muara Kaman - Riyadi, Husni (Jurnal Penelitian dan Pendidikan IPS, 2025)
This research aims to develop and determine the feasibility of interactive media in class VIII social studies subjects that can be used to support the learning process. The research method is Research and Development (R&D) with the ADDIE development model namely analysis, design, development, implementation and evaluation. This research was carried out from January to February 2024. While the object of the research was interactive powerpoint media. This data collection technique uses questionnaires and interviews which are analyzed descriptively. The results of this research are interactive learning media for class VIII social studies subjects (1) the results of validation by material experts are included in the assessment criteria "Very Feasible", (2) the results of media expert validation are included in the assessment criteria "Very Feasible", (3) the results of small group trials are included in the assessment criteria "Very Feasible" and (4) the results of large group trials are included in the assessment criteria "Very Feasible".Conclusion, PowerPoint which is used as an interactive learning media in class VII social studies subjects is "worthy" of use.